(untitled) (Conferencea, 2023)
Chronic venous insufficiency is one of the most common pathologies in the world. According to statistics, it occurs from 10-15% in men, 20-25% in women. The most common lesion of large joints is osteoarthritis. In Republic of Uzbekistan, up to 10% of the population suffers from it, mostly the elderly. Recently, more and more studies have appeared in the literature on the combination of these two pathologies. According to some studies, the addition of chronic venous insufficiency significantly affects the quality of life of patients with knee osteoarthritis.